2022
DOI: 10.3389/fonc.2022.836882
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetic Ropivacaine Exhibits Therapeutic Effects in Cancers

Abstract: Despite the significant progress in cancer treatment, new anticancer therapeutics drugs with new structures and/or mechanisms are still in urgent need to tackle many key challenges. Drug repurposing is a feasible strategy in discovering new drugs among the approved drugs by defining new indications. Recently, ropivacaine, a local anesthetic that has been applied in clinical practice for several decades, has been found to possess inhibitory activity and sensitizing effects when combined with conventional chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…Besides, ropivacaine has been found to have inhibitory activity and sensitizing effects when used in combination with conventional chemotherapeutics toward cancer cells, but the speci c mechanism remains unclear [27]. Ropivacaine inhibited the growth and progression of various tumors through multiple pathways, a study conducted by Baptista-Hon et al reported that ropivacaine blocked the NaV1.5 VGSC in colon cancer cells to inhibit the invasion [28], and it also has signi cant antitumor effects on primary (SW480) and metastatic (SW620) colon cancer cells [29], those studies suggested that ropivacaine has a potential application in controlling colon cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ropivacaine has been found to have inhibitory activity and sensitizing effects when used in combination with conventional chemotherapeutics toward cancer cells, but the speci c mechanism remains unclear [27]. Ropivacaine inhibited the growth and progression of various tumors through multiple pathways, a study conducted by Baptista-Hon et al reported that ropivacaine blocked the NaV1.5 VGSC in colon cancer cells to inhibit the invasion [28], and it also has signi cant antitumor effects on primary (SW480) and metastatic (SW620) colon cancer cells [29], those studies suggested that ropivacaine has a potential application in controlling colon cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…21 Ropivacaine has an antitumor role in various human tumors. 22 However, the ropivacaine role in ovarian cancer remained uncertain. In this study, we treated ovarian cancer cell lines with different doses of ropivacaine and demonstrated that ropivacaine inhibited ovarian cancer cell growth, implying that ropivacaine might exert a protective role in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-clinical case seemed strong, with LAs suppressing the viability and migratory capacity of breast cancer cells, dependent on the concentration and duration of drug application [ 12 , 13 , 14 , 15 ]. At least a part of the suppressive effect of LAs could occur via VGSC inhibition [ 16 ]. Disappointingly, however, regional anesthesia with lidocaine during tumor resection did not appear to have a significant effect on breast cancer outcomes including recurrence [ 17 ].…”
Section: Therapeutic Modalitiesmentioning
confidence: 99%